(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Introduction: The toddler period is a very important period in the growth and development process, because it determines the success of a child’s growth and development in the following period. Data obtained from Posyandu Mayang Terurai Teluk Bunian Village in August 2023, from 23 mothers of toddlers who visited, found 13 mothers of toddlers who complained that their children had appetite problems. Objective: The aim of this research is to determine the effect of acupressure on increasing appetite in toddlers aged 1-5 years at Posyandu Mayang Terurai, Teluk Bunian Village, Pelangiran District. Method: This research design uses pre experimental by design one group pretest dan posttest. The population in this study were toddlers aged 1-5 years with a sample of 19 people. The research uses observation sheets for data analysis using tests t-test. Results: The results of the study showed that before being given acupressure the majority of respondents had poor appetite (84.2%), after being given acupressure the majority of respondents had sufficient appetite, numbering 11 respondents (57.9%). There is an effect of acupressure on increasing appetite in toddlers 1-5 years old p-value 0,000 <0,005. It is recommended that community health centers provide acupressure training to health workers at Posyandu so that they can routinely provide acupressure to increase the appetite of visiting toddlers. to Posyandu.